Roof breaking characteristics and mining pressure APPEARANCE laws in close distance COAL seams - Xuping Li; Yanqing Liu; Xiaopeng Ren; Xiangye Wu; Chenhong Zhou (Energy Exploration & Exploitation, 2023)
In order to obtain lower coal seam mining of roof breaking characteristic and the law of mine pressure appearance in the close distance coal seams, this paper takes working face 6101 of a mine as the engineering background, and studies the roof breaking characteristics and pressure law in close distance coal seam through theoretical analysis, numerical simulation and engineering verification, which provides the basis for roof control in lower coal seam mining. The results show that the maximum failure depth of 4# coal seam mining on floor is 8.28 m. The lower coal seam mining roof forms a “loose-block” structure, and the main roof fracture step distance is 44.61 m. The UDEC simulation shows that the initial weighting intensity of 6# coal seam is large, and the first weighting distance step is about 40 m. The hydraulic support with the highest working resistance should be chosen based on the roof pressure analysis, and the weighting is frequent. The hydraulic support with higher working resistance should be selected through the analysis of roof pressure, some control measures should be taken to strengthen the organization and management, and prevent the occurrence of roof disasters. The roof is effectively controlled through engineering verification. The study further recognizes the laws of mining pressure appearance in lower coal seam of close distance coal seam, and provides experience for similar mine mining.